2020
DOI: 10.3389/fbioe.2019.00489
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Nano-Drug Delivery System in Treatment of Cardiovascular Diseases

Abstract: Cardiovascular diseases (CVDs) have become a serious threat to human life and health. Though many drugs acting via different mechanism of action are available in the market as conventional formulations for the treatment of CVDs, they are still far from satisfactory due to poor water solubility, low biological efficacy, non-targeting, and drug resistance. Nano-drug delivery systems (NDDSs) provide a new drug delivery method for the treatment of CVDs with the development of nanotechnology, demonstrating great ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(83 citation statements)
references
References 169 publications
(132 reference statements)
0
71
0
Order By: Relevance
“…Nanomaterials have been explored as drug delivery carriers for localized and controlled delivery of drugs to the target site. In cardiovascular medicine, conventional drugs or novel synthetic compounds are delivered to reduce atherosclerotic lesion formation, promote angiogenesis in ischemic tissues and improve the remodelling process in the damaged organs [ [68] , [69] , [70] ]. In the emerging area of nanotechnology, carbon allotropes are considered as one of the cardinal classes, which have gained significant attention in drug delivery applications [ 71 , 72 ].…”
Section: Application Of Cnms In Cardiovascular Tissue Engineeringmentioning
confidence: 99%
“…Nanomaterials have been explored as drug delivery carriers for localized and controlled delivery of drugs to the target site. In cardiovascular medicine, conventional drugs or novel synthetic compounds are delivered to reduce atherosclerotic lesion formation, promote angiogenesis in ischemic tissues and improve the remodelling process in the damaged organs [ [68] , [69] , [70] ]. In the emerging area of nanotechnology, carbon allotropes are considered as one of the cardinal classes, which have gained significant attention in drug delivery applications [ 71 , 72 ].…”
Section: Application Of Cnms In Cardiovascular Tissue Engineeringmentioning
confidence: 99%
“…As evident from earlier studies, nano-based theranostics were found to influence the prognosis of atherosclerosis, angiogenesis and other CVDs by sensitive detection of pathophysiological conditions and also infer appropriate therapeutic measures [ 124 ]. The efficacy of nanotheranostics in CVDs lies in the early and sensitive detection of CVDs associated with pathophysiology, controlled and localized drug delivery, and prolonged therapeutic effect [ 125 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…While a few other physical stimuli such as light, heat, and ultrasound have been proposed or implemented for treating these conditions, shear stress as a mechanical trigger has the advantage of being endogenous and site‐specific to the bleeding or pathological location. [ 27–29 ] This review provides a critical literature survey of research from the past decade on shear‐triggered nanocarriers for drug delivery. This review will primarily focus on the formulations of the nanosystems and their shear response mechanisms, as opposed to previous reviews which focus more on the physiological and translational aspects of shear‐sensitive DDSs.…”
Section: Introductionmentioning
confidence: 99%